DEPRESSION AND ASSOCIATED FACTORS: A CROSS-SECTIONAL STUDY USING BECK DEPRESSION INVENTORY - Athar, Husnain; Mukhtar, Neha; Shah, Sher; Mukhtar, Fatima (Journal of Ayub Medical College Abbottabad, 2017)
Background: Mental health disorders are becoming an increasingly common occurrence worldwide and present a major public health concern. Depression has been recognized as a major contributor in mental health disability burden. This study aims to determine the frequency of depression among individuals presenting at a rural health facility in Lahore and to identify the risk factors associated with it. Methods: A cross sectional study was conducted at Rural Health Centre Kahna nau, Lahore from January to April 2017. A sample of 384 consenting individuals presenting at the rural health facility were selected through consecutive sampling technique. Beck Depression Inventory (BDI), was used to assess the level of depression amongst the respondents. We categorized the BDI score for this study into BDI ‰¥20 as depressed and BDI <20 as non-depressed. Data was entered and analysed by using SPSS 16.0. Chi-square test was carried out to identify factors associated with depression, significant at a p-value of ‰¤0.05. Results: Out of total, 258 (69.5%) respondents were males with 197 (53%) in age category of 25-44 years. BDI scale showed 84 (23%) respondents to be suffering from depression. Age (p=0.002), income (p=0.003), marital status (p=0.023), educational status (0.011), family structure (p=0.041), history of hospitalization (p=0.003), smoking status (0.012) and co-morbidity (p=0.001) were significantly associated with depression. Conclusion: Our study found a substantial proportion of patients' who were suffering from depression. Age, income, marital status, educational qualification, family structure, co-morbidity and smoking status were significantly associated with depression. Keywords: Depression; Rural health centre; Beck Depression Inventory; Mental health